Plugging the patient evidence gap: what patients with swallowing disorders post‐stroke say about thickened liquids*. Issue 1 (16th June 2017) - McCurtin, Arlene; Healy, Chiara; Kelly, Linda; Murphy, Fiona; Ryan, Jean; Walsh, Joanne
Abstract: Background: Oropharyngeal dysphagia post‐stroke is well known, with its presence increasing the risk of poor outcomes in particular aspiration and aspiration pneumonia. Management to minimize the risk of aspiration and improve swallow safety post‐stroke includes the treatment of thickened liquids (TL), an established bolus modification intervention. Despite widespread use, there is a lack of robust empirical evidence and minimal patient evidence as to the experience and acceptability of using thickeners by people who experience dysphagia after a stroke. Aims: To explore people with swallowing disorders post‐stroke experiences of and acceptability regarding the bolus modification treatment of thickened liquids. Methods & Procedures: A qualitative, descriptive study exploring the experiences of individuals given TL after their stroke. A purposive sample of 14 adults was obtained with data collection and generation through the medium of individual semi‐structured interviews. Inductive thematic analysis was used to analyse the data. Outcomes & Results: Three overarching themes of 'uncertainty', 'an unpleasant experience' and 'a trade‐off' were identified. These themes highlight that participants disliked TL and this dislike may have impacted clinically in terms of adherence, hydration and quality of life. Lack of sensory appeal was important in framing patient dislike. Participants' involvement in and understanding of reasons for prescription of TL was poor leading to uncertainty regarding the treatment. Notwithstanding, some participants felt it was necessary for their stroke recovery. Conclusions & Implications: TL can be considered a burdensome treatment from multiple perspectives including product palatability, treatment uncertainty and treatment adherence issues. Despite intensely disliking this treatment, some patients ultimately understand why the treatment is prescribed. Improvements in product palatability are required in order to improve adherence and patient quality of life. Consideration of other treatment options and newer products to manage aspiration post‐stroke is also warranted. Abstract : Video Abstract .